Oscillometric measurement of the ankle-brachial index and the estimated carotid-femoral pulse wave velocity improves the sensitivity of an automated device in screening peripheral artery disease - Fendrik, Krisztina; Biró, Katalin; Endrei, Dóra; Koltai, Katalin; Sándor, Barbara; Tóth, Kálmán; Késmárky, Gábor (Frontiers in Cardiovascular Medicine, 2023)
Background and aims To overcome the time and personnel constraints of the Doppler method, automated, four-limb blood pressure monitors were recently developed. Their additional functions, such as measuring the estimated carotid-femoral pulse wave velocity (ecfPWV), have been, thus far, less studied. We aimed to compare the sensitivity and specificity of different ankle-brachial index (ABI), toe-brachial index (TBI), and ecfPWV measurement methodologies to evaluate their contribution to peripheral artery disease (PAD) screening. Methods Among 230 patients (mean age 64 ± 14 years), ABI measurements were performed using a Doppler device and a manual sphygmomanometer. The Doppler ABI was calculated by taking the higher, while the modified Doppler ABI by taking the lower systolic blood pressure of the two ankle arteries as the numerator, and the higher systolic blood pressure of both brachial arteries as the denominator. The automated ABI measurement was carried out using an automatic BOSO ABI-system 100 PWV device, which also measured ecfPWV. TBI was obtained using a laser Doppler fluxmeter (Periflux 5000) and a photoplethysmographic device (SysToe). To assess atherosclerotic and definitive PAD lesions, vascular imaging techniques were used, including ultrasound in 160, digital subtraction angiography in 66, and CT angiography in four cases. Results ROC analysis exhibited a sensitivity/specificity of 70.6%/98.1% for the Doppler ABI (area under the curve, AUC = 0.873), 84.0%/94.4% for the modified Doppler ABI (AUC = 0.923), and 61.5%/97.8% for the BOSO ABI (AUC = 0.882) at a cutoff of 0.9. Raising the cutoff to 1.0 increased the sensitivity of BOSO to 80.7%, with the specificity decreasing to 79.1%. The ecfPWV measurement (AUC = 0.896) demonstrated a 63.2%/100% sensitivity/specificity in predicting atherosclerotic lesions at a cutoff of 10 m/s. Combining BOSO ABI and ecfPWV measurements recognized 89.5% of all PAD limbs. Conclusion The combined BOSO ABI and ecfPWV measurements may help select patients requiring further non-invasive diagnostic evaluation for PAD. The user-friendly feasibility may make it suitable for screening large populations.